ANALYSIS OF THE INTERREGIONAL TRADE OF AGRICULTURAL COMMODITIES IN WEST SUMATERA, INDONESIA - Salfadri .; Abubakar Hamzah; Nazamuddin .; Sofyan Syahnur (Aceh International Journal of Social Science, 2015)
This study aims to investigate factors affecting interregional trade of agricultural commodities between regions in West Sumatera, Indonesia. For this purpose, this study use modified gravity model. There are four commodities that represent interregional trade of agricultural commodities in this study, namely: rice, chicken egg, broiler and fresh sea fish. This study uses cross section data of the 15 regencies/city in West Sumatera. The data is obtained from survey to wholesaler group of agricultural commodities in West Sumatera (primary data). The result of this study shows that factors affecting interregional trade in West Sumatera are: the difference in price (for commodities: rice, chicken egg and broiler), transportation costs (for commodities: broiler and fresh sea fish).